Family farm: Solution for sustainable development of rural area - Eduard Alexandru Dumitru; Laurenţiu Ionuţ Petre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
At present, in Romania there is no clear definition of the concept of family farm, and at the level of the European Union, the definition of family farms differs significantly depending on the characteristics of each country. At the same time, there is no classification of these types of farms, depending on the economic dimension, so that no solutions can be identified to support these types of farms, which can have a significant contribution on the development of rural areas. The purpose of the paper is to define the family farm and to determine their economic dimension, depending on the number of members involved in the activity of the farm. Depending on the minimum / average wage per economy, the lower and upper limits of classification of farms among family-type farms were determined.
Keywords: Q10; Q12; Q14; Q19; 330; family farm; rural development; Romania; sustainable